The prevalence and burden of health problems in male senior ice hockey: a prospective study in the Norwegian professional league - Nordstrøm, A.; Bahr, R.; Talsnes, O.; Clarsen, B. (British Journal of Sports Medicine, 2021)
Background As previous epidemiological studies in elite ice hockey have focused on acute time-loss injuries, little is known about the burden of overuse injuries and illnesses in ice hockey.